2021
DOI: 10.4995/wrs.2021.14623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lighting schedule, intensity, and colour on reproductive performance of rabbit does

Abstract: <p>In order to establish a lighting regime suitable for rabbit farms in East China, the effects of lighting schedule, intensity and colour on the reproductive performance of rabbit does were evaluated by three experiments, respectively. In experiment 1, does were exposed to different lighting schedules: 16L:8D-continuous, 16L:8D-18d (6 d before artificial insemination (AI) to 12 d post-AI), 16L:8D-6d (6 d before AI to the day of AI) and 12L:12D-continuous. In experiment 2, does were exposed to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The influence of light colours is mostly due to differences in light wavelengths. Wu et al [ 22 ] found that light colour had no discernible effect on the conception and kindling rates of female rabbits, but in this large sample study, we discovered that red and white light affected the conception and kindling rates and increased the number of kits at birth (total litter size and live litter size) ( p < 0.05, Table 2 ). The effects of red light on litter size and litter weight at weaning were superior to those of other light colours ( p < 0.05, Table 2 ).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The influence of light colours is mostly due to differences in light wavelengths. Wu et al [ 22 ] found that light colour had no discernible effect on the conception and kindling rates of female rabbits, but in this large sample study, we discovered that red and white light affected the conception and kindling rates and increased the number of kits at birth (total litter size and live litter size) ( p < 0.05, Table 2 ). The effects of red light on litter size and litter weight at weaning were superior to those of other light colours ( p < 0.05, Table 2 ).…”
Section: Discussionmentioning
confidence: 58%
“…Data were compared using one-way repeated analyses of variance (ANOVAs, SPSS software version 22.0) with Bonferroni post hoc tests. Simultaneously, nonparametric chi-square testing was used to analyse conception and kindling rates, as well as preweaning mortality [ 22 ]. A statistically significant p value of 0.05 was considered.…”
Section: Methodsmentioning
confidence: 99%